Errr, is this the frontline? - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2002)
Growing demand for meat products from a burgeoning urban market is pushing a new force through West Africa, as in other parts of the world: the livestock revolution. The pressure this puts on scarce land resources lifting is raised by similar...